PENDIDIKAN DAN PEMBANGUNAN NASIONAL: 7 PROGRAM UNGGULAN DAN PRIORITAS KEMENDIKDASMEN - Abdul Hakim; Asep Anang Afandi; Ahmad Taufik Hidayat; Ihdi Fuadi; Aprilliantoni (STKIP Subang, 2025)
This study analyzes the effectiveness of the seven flagship and priority programs of the Ministry of Primary and Secondary Education (Kemendikdasmen) and examines their implications for strengthening national development based on human resource (HR) quality. Using a qualitative approach with a library research design, this study explores various policy documents, scientific publications, and official government reports to provide a comprehensive assessment of program consistency, implementation readiness, and policy relevance. The findings show that the seven programs teacher redistribution, performance management reform, the transformation of the New Student Admission System (SPMB), character strengthening through the 7 Habits of Excellent Indonesian Children, the application of deep learning pedagogy, the integration of coding and artificial intelligence into the curriculum, and the implementation of the Academic Ability Test (TKA) represent a strategic policy package aligned with the vision of Indonesia Emas 2045. These programs contribute significantly to three key pillars of national education development: equity, quality improvement, and relevance to 21st-century competence needs. However, their impact depends on regional governance capacity, infrastructure availability, teacher competence, and collaborative engagement across education stakeholders. Continuous monitoring, integrated data systems, and supportive policy ecosystems are required to ensure successful and sustainable implementation. Keywords: flagship programs, education policy, Kemendikdasmen, Indonesia Emas 2045, human resource development.